2021
DOI: 10.2478/orhu-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Wintering waterbird assemblage in an emerging wetland of West Bengal, India: characterization for conservation management

Abstract: Waterbirds constitute a prominent biota and reflect the ecosystem health and functionality of the freshwater wetlands. Documentation of the bird species assemblages of wetlands is therefore carried out as a part of monitoring of wetlands from a sustainability viewpoint. Using the emerging wetland of Purbasthali, West Bengal, India, as a model study area, the diversity of the associated bird species was estimated to supplement necessary information for conservation management of birds and ecosystems. The point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, wetland habitats across India face significant threats, including habitat loss, fragmentation, and degradation; water quality deterioration due to contamination; recreational pressures; and developmental activities (Kumar & Sharma 2018;Chakraborty et al 2021;Kaur & Brraich 2021;Mandal et al 2021;Yashmita-Ulman & Singh 2022;Anand et al 2023;Muralikrishnan et al 2023). The Dighal wetlands are no exception, as they support a diverse community of winter migrants and species of global conservation concern, all of which are vulnerable to various anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, wetland habitats across India face significant threats, including habitat loss, fragmentation, and degradation; water quality deterioration due to contamination; recreational pressures; and developmental activities (Kumar & Sharma 2018;Chakraborty et al 2021;Kaur & Brraich 2021;Mandal et al 2021;Yashmita-Ulman & Singh 2022;Anand et al 2023;Muralikrishnan et al 2023). The Dighal wetlands are no exception, as they support a diverse community of winter migrants and species of global conservation concern, all of which are vulnerable to various anthropogenic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Birds occupy several trophic levels in the nutrient cycle of wetland ecosystems (Kumar & Sharma 2018;Chakraborty et al 2021;Rai & Vanita 2021;Rajpar et al 2022;Yashmita-Ulman & Singh 2022). Wetlands are important for both resident and migratory birds.…”
Section: Introductionmentioning
confidence: 99%
“…The management of Kaptai National Park has evolved to address both conservation and community needs. The Integrated Protected Area Comanagement (IPAC) project, launched in 2009, integrates local communities into the park's stewardship (Chakraborty et al, 2021;Nolan & Callan, 2006; M. M. Smith et al, 2020). This project promotes the sustainable use of resources while protecting the park's ecological integrity, aiming to resolve con icts and enhance conservation efforts.…”
Section: Introductionmentioning
confidence: 99%
“…The Purbasthali wetland is an important repository of various resident and migratory water bird species as it provides favourable space for breeding, foraging, roosting and watering . Avifaunal diversity of Purbasthali wetland has been studied by Chowdhury (2017), , , Debnath et al (2018) and Chakraborty et al (2021). These works presented a checklist based on both water birds and terrestrial birds living around the wetland.…”
Section: Introductionmentioning
confidence: 99%
“…These works presented a checklist based on both water birds and terrestrial birds living around the wetland. Subsequently, 74 water bird species have been identified by however; Debnath et al (2018) found 86 species, Chowdhury (2017) reported 89 species while Chakraborty et al (2021) has identified 27 species. have emphasized how human intervention has reduced the diversity among waders.…”
Section: Introductionmentioning
confidence: 99%